Single‐cell RNA sequencing reveals immune microenvironment of small cell lung cancer‐associated malignant pleural effusion - Shuyan Wang; Jing An; Xueru Hu; Tingting Zeng; Ping Li; Jiangyue Qin; Yongchun Shen; Mei Chen; Fuqiang Wen (Thoracic Cancer, 2024)
Abstract We used 10 × genomics single‐cell transcriptome sequencing technology to reveal the tumor immune microenvironment characteristics of small cell lung cancer (SCLC) in a patient with malignant pleural effusion (MPE). A total of 8008 high‐quality cells were finally obtained for subsequent bioinformatic analysis, which were divided into 10 cell clusters further identified as B cells, T cells, myeloid cells, NK cells, and cancer cells. Such SCLC related genes as NOTCH1, MYC, TSC22D1, SOX4, BLNK, YBX3, VIM, CD8A, CD8B, and KLF6 were expressed in different degrees during differentiation of T and B cells. Different ligands and receptors between T, B and tumor cells almost interact through MHC II, IL‐16, galectin, and APP signaling pathway.